CAF Dimensions As Measures Of University Students’ Writing Proficiency In Arabic As A Foreign Language - Syaifullah Syaifullah; Rumpoko Setyo Jatmiko; Malia Fransisca; Ahdiyat Mahendra; Atin Kurniawati; Cahya Edi Setyawan (Ijaz Arabi Journal of Arabic Learning, 2026)
Writing in Arabic remains a persistent challenge for non-native university learners, primarily due to the interplay between structural limitations and affective barriers—an intersection that has received limited integrative investigation. This study aims to identify and analyze the main obstacles faced by students in Arabic academic writing using the CAF (Complexity, Accuracy, Fluency) framework, as conceptualized by Barrot and Agdeppa (2021), which serves as the primary analytical lens. A descriptive-qualitative approach was employed, involving textual analysis of student writing samples and thematic analysis of responses collected through a Google Form questionnaire. The findings reveal that students struggle to construct complex syntactic structures, maintain grammatical accuracy, and sustain coherent idea development. These three dimensions are interdependent and further exacerbated by psychological factors such as fear of making mistakes and low self-confidence. The study concludes that writing difficulties are not purely linguistic but are also shaped by affective and cognitive dimensions. Theoretically, this research contributes to a deeper understanding of the interrelationship between linguistic competence and psychological readiness in academic writing. Practically, the findings offer pedagogical implications for designing more integrative writing instruction that emphasizes syntactic exploration, functional grammar internalization, and the development of metacognitive strategies.